Rule - Based Modeling and Computing on the Semantic Web 5th International Symposium, RuleML 2011? America, Ft. Lauderdale, FL, Florida, USA, November 3-5, 2011. Proceedings - Olken, Frank; Palmirani, Monica; Sottara, Davide (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the International RuleML Symposium, RuleML 2011-America, held in Fort Lauderdale, FL, USA, in November 2011 - collocated with the 22nd International Joint Conference on Artificial Intelligence, IJCAI 2011. It is the second of two RuleML events that take place in 2011. The first RuleML Symposium, RuleML 2011-Europe, has been held in Barcelona, Spain, in July 2011. The 12 full papers, 5 short papers and 5 invited track and position papers presented together with 3 keynote speeches were carefully reviewed and selected from numerous submissions. The accepted papers address a wide range of rules, semantic technology, and cross-industry standards, rules and automated reasoning, rule-based event processing and reaction rules, vocabularies, ontologies and business rules, cloud computing and rules, clinical semantics and rules.